Implementasi Lesson Study pada Pengajaran IPS Kelas Tinggi - Soebijantoro, Soebijantoro (Jurnal Pendidikan, 2011)
The graduation ratio of Electronics I subject passes 95% and more than 75% of the students get B. The Electronics I subject, which mainly discusses diode and transistor, has become the prerequisite one for the next Electronics II containing underlying theories for the advanced apllication of them. It is prdicted that the students have perceived a strong basis for the understanding of Electrobics II materials. This assumption leads to an idea of developing the students independence in learning Electronics II subject. The strategy is taken up by giving independent tasks so as to present them before the class. The studentsâ proficiency can be noted from the discussion process. The result of analysis shows that the students can achieve good result almost without lecturers assistence. In each of presentation, 80% of the arising problems can be resolved well without lectrerâs assistence, which then means that the students independence can be achieved under this learning technique. The pasasing grade of the subject can be proudly acheived by 98.72% of the students. Out of 78 students, 8 of them (10.26%) get A, 59% of them (76.92%) get B, and 10 of them (12.82%) get C, and 1 student (1.28) gets D. The overall achievement shows that independent learning can be built upon presentation technique.Keywords: discussion, independent learning, acheivement